Phytochemical Screening of Acetone Extract of Rambai Leaves (Baccaurea motleyana) and Its Bioactivity as an Antibacterial Against Escherichia coli and Staphylococcus aureus - Fransiska, Destalia; Roanisca, Occa; Nurhadini, Nurhadini (Jurnal Pijar Mipa, 2024)
Bacteria are one of the organisms that may cause disease in the human body. Some bacteria which often infect the human body are Escherichia coli and Staphylococcus aureus. Both bacteria are pathogenic and possibly lead to various diseases such as diarrhea, urinary tract infections, and lung infections that have the potential to result in death. Treatment of infections caused by these bacteria can be done by giving antibiotics as therapy or a quick cure against infection. The use of antibiotics has side effects that result in resistance. Therefore, it is necessary to screen bioactive compounds with bioactivity as better antibacterial agents so that they can be developed into drugs that can cure diseases caused by bacteria. It is urgent to utilize natural antibacterials from plants to treat bacterial infections. This research aims to obtain the compound content, the total phenolic, and antibacterial activity of acetone extract of rambai leaves, so this research focused on rambai leaf acetone extract phytochemical content, total phenolic content, and antibacterial activity examination. Then, Phytochemical testing of rambai leaf acetone extract (Baccaurea motleyana) shows rambai leaves contain alkaloid compounds, tannins, flavonoids, saponins, steroids, and terpenoids that have the potential to be antibacterial. The examination of phenolic content was accomplished by using the Folin-Ciocalteau method. The total phenolic test results obtained were 68.63 mg EAG/g. Antibacterial testing was performed by implementing the disk diffusion method. Antibacterial testing of rambai leaf acetone extract Concentration of 20 %, 40%,60%, and 80%  showed consecutive results in inhibition zones of 3.86 mm, 6.48 mm, 6.55 mm, and 6.63 mm with weak to medium activity for E. coli bacteria. However, S. aureus  bacteria showed consecutive results in inhibition zones of 6.02 mm, 10.15 mm, 17.10 mm, and 19.46 mm with medium to intense activity. There has not been much research on rambai from Bangka Belitung, so there is an indispensable for further research regarding the total flavonoid and total alkaloid content of rambai leaves. Research may also carried out using a variety of solvents.